2020
DOI: 10.1097/cm9.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Differences of maternal mortality rate between Shanghai and New York city from the perspective of regulatory policy

Abstract: Background Regulatory policy (RP) is known as a major factor to improve health care system performance. A significant difference in maternal mortality rates (MMRs) was observed between New York city (NYC) and Shanghai (SH), both first-class international metropolises. This study aims to adopt a quantitative evaluation model to analyze whether RP differences contribute to the different MMRs of the two cities. Methods Based on collection of all publicly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The latter was chosen as an indicator in the government performance evaluation system. In addition, SH always paid attention to the supervision of the process and effectiveness of WHSs [ 40 ]. For example, the obstetric emergency care grading system and responsibility chain was implemented for the management of critically ill pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was chosen as an indicator in the government performance evaluation system. In addition, SH always paid attention to the supervision of the process and effectiveness of WHSs [ 40 ]. For example, the obstetric emergency care grading system and responsibility chain was implemented for the management of critically ill pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found disparity between natives and migrants in SH, and analyzed the barriers in maternal health service utilization in 2009 [ 39 ]. Li et al analyzed and compared the perspective of regulatory policies on MMRs control in SH and NYC, concluding that the more comprehensive and effective regulatory policies had a more substantial impact on MMR control from 2006 to 2017 [ 40 ]. We have seen few studies on the impact of WHSs delivery on MMRs in the two cities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous research has shown that the soundness of RPs can effectively improve unhealthy lifestyles among patients with hypertension [7]. Similarly, the soundness of RPs has also been found to promote maternal and child health [25]. In this context, regions with better RPs have more effective PCCDs, particularly when RPs are more comprehensive and cover a range of aspects, such as diet management and the living environment.…”
Section: Discussionmentioning
confidence: 99%
“…to reflect the importance of RPs. Furthermore, the mechanism requires supervision by external restraint mechanisms for the implementation of the policies [25]. Therefore, four quantitative indicators were adopted.…”
Section: Measurements 221 the Soundness Of Rpsmentioning
confidence: 99%
See 1 more Smart Citation